Modern Computer Studying Means of Teaching Ukrainian Language in Higher Education Institution - Tetіana Yasak (Pedagogical Discourse, 2014)
The article deals with the didactic potential of modern computer studying program of Ukrainian language, and its classification, according to the informational and educational features is given. Psychological and pedagogical benefits and lingvodidactic feasibility of universal computer studying program of professional Ukrainian language are proved in the article. The article considers the features of modern computer studying program of universal type that contribute to constant updating of their content by independent creation and use of new didactic components of the educational process by the participants. According to the monitoring of the results we revealed that the computer studying program provides a significant intensification of the process of learning through operational relationship between the source of educational information and the student, the implementation of individual learning paths in linguistic and psychological sphere is to be taken into consideration, as well as the language and speech competence of the students and adaptation rate of presentation of the educational material to the rate of its learning. It is concluded that the adaptive capacity of the computer studying program allows the teacher to work with students of different levels at the same time, taking into account their scope of knowledge and potential, common mistakes, abilities and linguistic interests.